Design of novel algorithms for 3D human head modeling and expression synthesis - Chen, Chen (2010)
The efficiency and robustness to synthesize personalized facial expression is a chal-lenging part in research of computer facial animation. To overcome this challenge, two problems have to be addressed. Facial Shape Modeling: Anaccurate face shape model is required to mimic the 3D geometry of real human face surface. Accurate modeling is a tedious work and we need to accelerate the modeling process. Robust Physical Simulation: Efficient dynamic deformation on facial skin driven by face anatomical structure is a key solution to synthesize realistic facial ex-pressions. The deformation modeling should support real-time performance with the ability to represent skin elastic properties.